Standardization Vs Adaptation of Marketing Strategy - A Qualitative Study - Ramesh, G. (Indian Journal of Marketing, 2011)
Standardized Marketing Strategy universally has resulted in a mixed outcome - Success as well as failure. Specifically, the success or failure depends on the following questions (a) Is the Standardization Marketing Strategy approach workable, irrespective of the country of origin? (b) Do the brand names play a significant role with regard to the cultural vignettes of a country? (c) How is the Packaging issue taken care of globally? (d) Can the same Advertising campaign be used universally? Why and Why Not?. The above questions have surfaced a way for a debate whether Standardization or Adaptation is the need for an effective Marketing Strategy. This paper attempts, in a qualitative approach such as in-depth interviews, brainstorming sessions, focus group, to establish some relationships between select parameters and the Standardization issues. This paper also figures out arguments and based on those arguments, specific hypotheses were defined, which could be tested as a future scope of study.